Environmental Theatre As A Platform For Education And Social Mobilization: A Case Study Of Urban Waste Issue Performances - Iriana Bakti; Soe Thu Zaw Zaw; Ikhwanul Ihsan Armalid (Yayasan Adra Karima Hubbi, 2025)
challenges in effectively engaging the public and catalysing behavioural change, particularly regarding pervasive issues like urban waste. Environmental theatre, an arts-based approach that uses performance to communicate ecological themes, offers an alternative pedagogical tool that can foster deeper cognitive and emotional connections to environmental problems. Purpose. This study aims to investigate the effectiveness of environmental theatre as a dual-purpose platform for enhancing public ecological awareness and mobilizing community action on urban waste management. Method. A qualitative case study methodology was employed, focusing on a series of public theatre performances addressing plastic waste in Bandung, Indonesia. Data were gathered through participant observation, post-performance semi-structured interviews with audience members (n=45), and a focus group discussion with the theatre troupe. A thematic analysis was used to identify key outcomes and audience responses. Results. The findings indicate that the immersive and narrative-based format of the theatre performances significantly increased audience members' emotional engagement with and intellectual understanding of the urban waste crisis. A substantial majority of interviewees (over 85%) reported a heightened sense of personal responsibility and expressed a stronger intention to adopt pro-environmental behaviours, such as waste segregation and reducing consumption. Environmental theatre serves as a highly effective and potent medium for both environmental education and social mobilization. Conclusion. By moving beyond simple information dissemination to create an embodied, affective experience, it successfully fosters the critical consciousness and motivational impetus required to translate awareness into tangible individual and collective action.